A Radiological study of the Right Lung - Oosthuizen, Sarel Francois (Department of Medicine, 2020)
The purpose of this thesis is to illustrate the author's observations on radiological investigations of the right lung both in the living body and at post-mortem, and to describe certain aspects of anatomical, clinical, pathological and radiological interest.